Possibilities of Developing Tourism in the Southern Regions of Uzbekistan (In the Case of Kashkadarya, Surkhandarya) - Eralov Azamat Jomurodovich (Peerian Journals Publishing, 2022)
This article will talk about the prospects for the development of tourism in the southern regions of the Republic of Uzbekistan. The author, relying on archaeological data, archival documents and written sources, analyzed the problem on the basis of existing scientific and historical literature and studied the existing peculiarities of the development of the tourism sector in the southern regions of the Republic of Uzbekistan (on the example of Kashkadarya, Surkhandarya).
Keywords: Tourism; tourists; pilgrimage; opportunities